Absolute Komplexität in der Nominalflexion Althochdeutsch, Mittelhochdeutsch, Alemannisch und deutsche Standardsprache - Baechler, Raffaela (Morphological Investigations, 2017)
This book provides a quantifiable measure and analysis of absolute complexity in the nominal inflection of 17 Alemannic dialects, of standard German as well as of Middle and Old High German. The data is based on grammatical descriptions. What can be interpreted as being more or less complex in a language system is deduced from LFG (Lexical-Functional Grammar) and from an inferential-realisational morphological framework. The tool to measure inflectional complexity is also developed from these frameworks. Variation in the inflectional complexity is analysed based on the following factors: diachrony, isolation, language contact, standardisation, and dialect groups.